The rationale for targeting TGF‐β in chronic liver diseases. (12th March 2016) - Giannelli, Gianluigi; Mikulits, Wolfgang; Dooley, Steven; Fabregat, Isabel; Moustakas, Aristidis; ten Dijke, Peter; Portincasa, Piero; Winter, Peter; Janssen, Richard; Leporatti, Stefano; Herrera, Blanca; Sanchez, Aranzazu
Abstract: Background: Transforming growth factor (TGF)‐β is a pluripotent cytokine that displays several tissue‐specific biological activities. In the liver, TGF‐β is considered a fundamental molecule, controlling organ size and growth by limiting hepatocyte proliferation. It is involved in fibrogenesis and, therefore, in worsening liver damage, as well as in triggering the development of hepatocellular carcinoma (HCC). TGF‐β is known to act as an oncosuppressor and also as a tumour promoter in HCC, but its role is still unclear. Design: In this review, we discuss the potential role of TGF‐β in regulating the tumoural progression of HCC, and therefore the rationale for targeting this molecule in patients with HCC. Results: A considerable amount of experimental preclinical evidence suggests that TGF‐β is a promising druggable target in patients with HCC. To support this hypothesis, a phase II clinical trial is currently ongoing using a TGF‐β pathway inhibitor, and results will soon be available. Conclusions: The identification of new TGF‐β related biomarkers will help to select those patients most likely to benefit from therapy aimed at inhibiting the TGF‐β pathway. New formulations that may provide a more controlled and sustained delivery of the drug will improve the therapeutic success of such treatments.